A Study On The Teaching Learning Process Of Writing IiAt English Department Of Muhammadiyah University Of Surakarta - Amintarsih, Dwi (2012)
The study is aimed at observing the teaching learning process of writing II at English department of Muhammadiyah University of Surakarta. The objective of the study is to describe teaching learning process of writing at English Department of Muhammadiyah University of Surakarta. In this research, there are six component of teaching learning process that the writer analyze, such as: (1) Learning Objective. (2) The Syllabus. (3) The Material. (4) The Method, which is included: (a) Classroom Procedure (b) Media (c) Teacher's Role (d) Student's Role. (5) The Evaluation System. (6) The Strength and Weakness. The type of the study is descriptive qualitative especially ethnography. In this research, the data are derived from event, informant, and field note. There are three techniques of collecting data, namely: observation, interview, and document. The techniques of analyzing data are reduction of the data, display the data, and verification or drawing conclusion. The result of the study, such as: (1) Learning objective of writing is to increase the students' ability in writing skill. (2) The type of syllabus is task based syllabus. (3) The material used is printed material, the materials are genre text and vocabulary. (4) The method used is eclectic method, they are grammar translation method and genre based approach. (a) The procedures of teaching learning process are consists of pre activity, main activity and post activity. (b) The media used in teaching learning process is handout, which makes the students understand well (c) The teacher's roles are facilitator, classroom manager, instructor, consultant, and evaluator. (d) The students' role is as the subject. (5) The evaluation is composition test and objective test. (6) The strength is the students more active, the teacher lets them to be independent learner. The weakness is the target language is used rarely.